ASSESSMENT OF GENETIC VARIABILITY IN RICE (ORYZA SATIVA L.) FOR YIELD AND NUTRITIONAL TRAITS: ASSESSMENT OF GENETIC VARIABILITY IN RICE FOR YIELD AND NUTRITIONAL TRAITS - GADI HARIPRIYA; T. HARITHA; B. KRISHNA VENI; C. N. NEERAJA (The Journal of Research ANGRAU, 2026)
The present study was conducted using 144 rice genotypes including five checks (BPT 5204, BPT 2841, Chittimuthyalu, Kalanamak, DRR DHAN 45) evaluated for 12 traits at Agricultural College Farm, Bapatla during kharif, 2024-25 using augmented block design. Analysis of variance revealed significant differences among genotypes for 12 traits, indicating substantial genetic variability with in the experimental material and hence can be exploited for future crop improvement programme. High genotypic and phenotypic coefficients of variation was observed for protein content (%), antioxidant activity (mgAAE/100g), Fe content (ppm), Zn content (ppm) and grain yield per plant (g), while plant height (cm), number of tillers per plant, number of productive tillers per hill and test weight (g) showed moderate GCV and PCV values. The PCV estimates were higher than GCV for all the characters indicating that substantial variation for these characters was contributed by environmental components. High heritability coupled with high genetic advance as percent of mean was recorded for plant height (cm), number of tillers per plant, number of productive tillers per hill, test weight (g), protein content (%), antioxidant activity (mgAAE/100g), Fe content (ppm), Zn content (ppm) and grain yield per plant (g) indicating that these traits are largely governed by additive gene action and hence direct selection of these traits for improvement of dependent variable (yield) may be rewarding.